Analisa Yuridis Independensi Komisi Pemberantasan Korupsi sebagai Lembaga Ekstra Konstitusional dalam Sistem Ketatanegaraan Indonesia - Farida, Alchansyah (UI Scholars Hub, 2024)
The Corruption Eradication Commission (KPK) was formed as a follow-up to the mandate of Article 43 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. The Corruption Eradication Commission exists as an answer to the less than optimal performance of the Police and Prosecutor's Office in eradicating corruption. Apart from that, the Corruption Eradication Commission exists as an independent state institution (not tied to any authority, be it executive, legislative or judiciary). However, after the enactment of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission, it had a huge influence on the KPK institution. The principles of independence of the Corruption Eradication Commission as characterized as a corruption eradication institution are increasingly being lost, the Corruption Eradication Commission has limited room for movement and is under executive power.